Voices of transition: sharing experiences from the primary school. Issue 7 (3rd October 2021) - Packer, Rhiannon; Thomas, Amanda; Jones, Cath; Watkins, Philippa
ABSTRACT: Transition has long been acknowledged to have an impact upon the academic, social and emotional development of learners, which can be long lasting in effect. Using an interpretive methodology, the voices of the three key stakeholders involved in primary education transition – learners, practitioners and parents/caregivers – were sought and recorded to inform good practice. Data were collected using online and paper questionnaires, interviews and focus groups. Findings concluded that to enable successful transition there is a need for all involved to: prepare and plan, engage in effective communication, foster positive relationships, and be responsive to individual needs.